6 - Les langues indigènes dans le processus de développement en Afrique Défis, opportunités et alternatives - Noël Obotela Rashidi (Africa Media Review, 2005)
This paper makes a link between processes of development and the use of indigenous languages. In fact, languages play an important role in transmitting messages, mobilising the population to appropriate themselves the process of development and the success of actions to undertake. In spite of opportunities, there are challenges and alternatives. The first challenge is related to the rethinking of the State. It is about establishing an efficient link between the state and the local community. The second challenge concerns the incitation to favour the involvement of populations at any process of development. The third is related to the choice of language or languages. The last is linked to the integration extolled by the African Union and the insertion of the continent in the globalisation line process. This plea for the promotion of indigenous languages speaks in favour of the setting up of a linguistic architecture not only of local languages limited to community spheres, but also unifying national languages without neglecting languages inherited from colonisation.